ANALISIS HUBUNGAN KOMPENSASI DENGAN KINERJA KARYAWAN RUMAH SAKIT PKU MUHAMMADIYAH TEMANGGUNG - Wiwik Dewi Sugiharti; Firman Pribadi (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2015)
The PKU Muhammadiyah Temanggung applies an integrated compensation system to its employees in order to motivate their spirit of work and productivity. Deep evaluation over this system is needed to value the employees peformance quality achievement as one of the factors to improve the work productivity in this institution. This research has an aim to analyse the connection between Financial Compensation and Non Financial Compensation with the Employees Performance in the PKU Muhammadiyah Hospital Temanggung. This quantitative descriptive research was run using the method of Cross Sectional which is the questionnaire means of measurement was applied. The sampling collection was conducted using Purposive Sampling technique against employees of the PKU Muhammadiyah Hospital Temanggung in the amount of 150 respondents who fulfill the criteria. The variables whitin this research consists of Financial Compensation, Non Financial Compensation, and also Employees Performance. The data analysis using Univariat and Bivariat Analysis applying Spearman Correlation Rank and Kendall Tau Test to comprehend the connection among variables. Improving the validity of research data the data source triangulation was done. This research emerging the conclusion that there is no significant connection between the Financial Compensation and the Employees Peformance in the phase of less significant, and also the existing connection between the Non Financial Compensation and the Employees Performance in the phase of weakness.